Assessing the impact of the recent warming in the East China Sea on a torrential rain event in northern Kyushu (Japan) in early July 2017 - Manda, Atsuyoshi; Iizuka, Satoshi; Nakamura, Hisashi; Miyasaka, Takafumi (Frontiers in Climate, 2022)
Sea surface temperature (SST) in the East China Sea (ECS) has undergone a rapid rise in recent decades, but the associated impact on extreme weather remains under debate. Here, using a cloud–permitting model, we assess the impact of the ECS warming observed since the 1980s on a torrential rain event that caused devastating floods and landslides in the Kyushu Island, western Japan, in July 2017. Without the increasing trends of SST and air temperature, the model cannot reproduce the observed extremely high amount of precipitation during the event, i.e., >700 mm/12-h. The SST increase is found more influential in determining the precipitation amount. Without the ocean warming, increases in precipitable water and horizontal moisture transport due to the atmospheric warming would not lead to precipitation increase during this event. The change in the amount of precipitation can be largely explained by the change in the updraft intensity of the convective system. Higher SST suppresses downward surface sensible heat flux and enhances upward latent heat flux along the paths of air parcels flowing into the convective system in this case. This increases the equivalent potential temperature in the lower troposphere, which enhances the convective available potential energy in the lower troposphere, leading to intensification of the convective system and thereby the increase of precipitation. The findings of this case study suggest an important role of the warming ECS in the intensification of torrential rain events around Japan and the necessity of further assessment of the role of the ocean warming in the torrential rains.